Microwave fluidized bed for biomass pyrolysis. Part I: Process design. (16th May 2017) - Adam, Mohamed; Beneroso, Daniel; Katrib, Juliano; Kingman, Sam; Robinson, John P.
Abstract: The production of bio‐oils from microwave pyrolysis has received increasing attention from bioenergy researchers, but no studies reported to date have proposed reliable solutions to avoid thermal runaway. The motivation of this paper is to develop and demonstrate a systematic methodology to exploit the benefits of microwave heating for biomass pyrolysis, and to overcome previously reported challenges of heating heterogeneity and thermal runaway. The multidisciplinary design methodology for a microwave fluidized bed system is presented, which is based on processing raw biomass without the need for added microwave susceptors. The design process considers the minimum fluidizing velocity of biomass particles, a heat‐transfer model to establish the power density requirements, and electromagnetic simulations to determine the optimal dimensions. It was found that a minimum power density of 54 MW m −3 was necessary to reach temperatures of 400 °C for particles with an average size of 600 µm at the minimum fluidization velocity (0.38 m s −1 ). Higher gas velocities required higher power levels; however, the energy efficiency of the process could be improved when using a high power at low gas velocities, with 1.07 kJ g −1 attainable at power densities in excess of 100 MW m −3 . A microwave fluidized bed system was subsequently designed, and shown to be effective in enabling pyrolysis whilst limiting heterogeneity and thermal runaway effects. Thermal runaway could be controlled by ensuring an appropriate fluidization regime to prevent liquid condensation and solid deposition within areas of high electric field intensity. The developed design opens opportunities for large‐scale production of bio‐oil using microwaves. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd